New separation method of metal/plastic micronized particles using travelling wave conveyors. Issue 5 (3rd September 2018) - Mahi, Imene; Messafeur, Radjaa; Belgacem, Abdelkader; Bellebna, Yassine; Louati, Hamza; Tilmatine, Amar
Abstract: The paper reports an experimental investigation for studying the movement dynamics and the separation of micronized particles on a poly-phase travelling wave conveyor (TWC). A digital balance and a sensitive electrometer controlled by Labview software were used to analyse the velocity and the material flow rate on a three-phase conveyor with respect to the variation of both the amplitude and the frequency of the applied voltage. It was found that about 80% of the particles mass move together in one single wave and that the electric charge gained by the particles increases with the intensity of the electric field. Moreover, preliminary experiments showed that it is possible to separate a granular mixture of plastic and copper micronized particles using a TWC. Successful experiments were carried out on micronized samples of both electric cable and electronic card wastes. High purity metal was recovered.